1962 the war that wasn`t - Verma, Shiv Kunal (New Delhi, 2016)
On 20 October 1962, high in the Himalayas, on the banks of the fast-flowing Nam Ka Chu, over 400 Indian soldiers were massacred, and the valley was overrun by soldiers of China's People's Liberation Army. Over the course of the next month, nearly 4,000 soldiers were killed on both sides, and the Indian army experienced its worst defeat ever.
Keywords: Sino-India border dispute 1962